Resensi Buku Dasar-Dasar Penerjemahan Umum - Fauziah, Hanny (Jurnal Penerjemahan, 2021)
Translation is the meaning interpretation of the source text to produce equivalent in the target text that communicates similar messages. The book of Dasar-dasar Penerjemahan by Haru and Andika explains clearly the meaning of a translator and the thirteenth (13th) basic competencies that must be owned by a translator, eighth (8) methods, and sixth (6) types of translation procedures, as well as two translation ideologies that can be used at the time of the translation process using simple explanations so that it is easily understood by beginner readers and newbi translators. Keywords: competencies, method, translation procedures, translation ideologies